An integrated approach for the design of a marine protected area network applied to mainland Portugal - Timonet, Diana (2022)
The high degree of marine habitat degradation and the depletion of marine resources has led to numerous calls and initiatives to increase the coverage of marine protected areas (MPAs). Currently, marine reserves (no-take areas) cover approximately 2.2% of the world's oceans whilst most calls and targets suggest protection levels should be between 20% and 30% in order to achieve both conservation and resource management objectives. In this study a systematic conservation planning framework was developed using ecological and socio-economic data. This framework was used to test different protection scenarios in Portugal. The current situation in mainland Portugal is alarming, with 0.2% of the waters under national jurisdiction included in MPAs and only 0.002% being marine reserves. Moreover, ecologically important habitats, such as seagrass beds and maerl beds, have less than 10% of their area protected. The solutions provided by Marxan, and subsequently improved with MinPatch, revealed that there is a need to considerably increase the area under protection. However, adequate protection could be achieved with a number of MPAs (between 5 and 14) similar to the number of already existing MPAs (n = 8). Different stakeholders (artisanal fisheries, industrial fisheries, and other human uses such as oil and gas, and offshore aquaculture) were considered in different scenarios, with the results of the multivariate analysis indicating that there are several solutions that satisfy all stakeholders. Therefore, the results of this study are a valuable starting point for the ongoing implementation process of an MPA network in Portugal since they integrate the most important stakeholders whilst also taking in consideration the ecological aspects. This framework can be applied elsewhere and can be easily amended whenever new information is available.